A model-driven approach for the verification of an adaptive service composition. (8th June 2020) - Zatout, Sara; Boufaida, Mahmoud; Benabdelhafid, Maya Souilah; Berkane, Mohamed Lamine
The development of web service compositions is a complex task that needs coherent mechanisms in order to maintain the quality of the provided business process and to satisfy user needs. This paper proposes a development process of an adaptable composed web service and mainly focuses on the reliability and the performance properties. It explores the model driven architecture transformation technique in order to formally model the whole service orchestration using the timed coloured Petri net formalism. The software CPN Tools offers, among others, the ASK-computational tree logic, the model checking technique and several monitors that will be exploited to describe and verify different properties at design time. They will also be used via access/CPN library in order to reason about the reconfiguration technique at runtime. An example of an identity card management process is given to prove the feasibility of the proposed solution.